Elemental accumulation in mango (Mangifera indica L.) as a function of maturity stage and variety. (21st August 2017) - Sinha, Rajni; Jaiswal, U. S.; Ahmad, M. Feza; Mishra, Praveen Kumar; Sinha, Suparna
ABSTRACT: Information about the nutritional status of a plant is a basic prerequisite for its adequate nutrition and is crucial to achieve high-yield productivity. Assessing the annual amount of nutrient that a tree needs to absorb in order to successfully complete a vegetative and reproductive growth is a fundamental step for developing rational fertilization in orchards. We are unaware of any report describing macro- and micronutrient dynamics in fruit at different growth stages of mango. Seven cultivars of mango (Dashehari, Langra, Mahmood Bahar, Menka, Sabri, Sundar Langra and Zardalu) were selected for the study. Different macronutrients such as nitrogen, phosphorus, potassium, calcium and magnesium (N, P, K, Ca, and Mg) and micronutrients such as iron, manganese, zinc and copper (Fe, Mn, Zn, and Cu) were analyzed at four growth stages, namelymarble stage, prestone formation stage, stone hardening stage and harvest stage. There was a significant variation in nutrient content of fruits throughout the developmental stages irrespective of cultivars. There was no definite trend of nutrient variation among cultivars but in general, most of the nutrients like N, P, K, Mg, Mn, Zn, and Cu were the highest at the marble stage, and Ca and Fe at the stone hardening stage.